PERAN GURU DALAM PENGELOLAAN KELAS UNTUK MENINGKATKAN PEMBELAJARAN AKIDAH AKHLAK - Wiwik Minda Ningsih; Resdianto Permata Raharjo (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Learning is a process of interaction between students and educators and learning resources in a learning environment. Learning will come alive depending on how the teacher manages the class well. Like the teacher at Abdul Wahid Hasyim Jombang Middle School, he manages the class well in learning Akidah Akhlak. Classroom management is needed to optimize learning. Therefore the teacher must have a role in managing the class including the teacher's skills in creating conducive learning conditions and the teacher's skills in controlling learning so that it is conducive again Improving the quality of learning aqeedah akhlaq has been carried out, both efforts to improve the quality of teachers in the field of aqeedah akhlaq itself as well as improving the quality of teachers by the principal as well as the teacher's role in improving the aqeedah akhlaq learning with students. The role played by the teacher is to improve material, use various methods, use facilities and conduct evaluations. In improving the learning of aqidah morals there are also driving and inhibiting factors. As for the driving factor is the high interest of students in the subject of aqidah morals while the inhibiting factor is the background of students who have different levels of intelligence that are not the same. Thus, to improve the learning of aqeedah morals, as teachers and principals, they strengthen their duties by carrying out various efforts and being able to solve the various obstacles they face. This study aims to find out more about the teacher's role in managing the class in improving the learning of the moral creed for students at SMP Ahmad Wahid Hasyim Jombang. To achieve the above research objectives, a research approach was used, namely qualitative research. Then the method used in this research is observation, and interviews.